Impact of Irrigation Ecology on Rice Production Efficiency in Ghana - John Kanburi Bidzakin; Simon C. Fialor; Dadson Awunyo-Vitor; Iddrisu Yahaya (Advances in Agriculture)
Irrigation production is a means by which agricultural production can be increased to meet the growing food demands in the world. This study evaluated the effect of irrigation ecology on farm household technical, allocative, and economic efficiency of smallholder rice farmers. Cross-sectional data was obtained from 350 rice farmers across rain fed and irrigation ecologies. Stochastic frontier analyses are used to estimate the production efficiency and endogenous treatment effect regression model is used to estimate the impact of irrigation ecology on rice production efficiency. The impact of irrigation ecology on technical efficiency is about 0.05, which implies farmers producing under irrigation ecology are more technically efficient in their rice production than those in rain fed production. The impact of irrigation ecology on allocative efficiency is about 0.33, which shows that farmers participating in irrigation farming are more allocatively efficient in their rice production than those in rain fed production. The impact on economic efficiency is about 0.23, meaning that farmers participating in irrigation farming are more economically efficient in their rice production than those in rain fed production. Irrigation ecology has positive impact on production efficiency; hence farmers should be encouraged to produce more under irrigation for increased yield and profit.